Updating Risk Level on Housing Resettlements of Mount Merapi Using a Visual Chart Examination - Noor Cholis Idham; Supriyanta Ir H Msi (Iconarp International Journal of Architecture and Planning)
Permanent housing resettlement (Huntap) on the slopes of Merapi from the 2010 great eruption supposedly has experienced development progress. Undergoing adjustments due to environmental circumstances, hazard knowledge, and people's understanding are inevitable and affect the safety performance of the shelter against volcanic hazards. Many dwellings are still in the most dangerous area, while the hazards will strike again sooner or later. This research intends to update Merapi Huntap's safety risks to mitigate volcanic disasters. We assessed the safety of 15 settlements and focused on calculating five selected Huntaps for their spatial and formal configuration to the dwellers' awareness. Detailed observation by a proposed visual chart method based on the hazard and degree of vulnerability discovered from hazard-prone zones (KRB). Resilience factors to safety, including access for evacuation, the dwelling, and community consciousness of disaster, discovered the disaster risk level. We found that disaster risk in Merapi's resettlement is still high; thus, the people and stakeholders need to pay more attention to the need for precautions. Mitigation should address the potential safety threats related to (1) Hazard-prone levels, (2) Spatial confusion for up-to-date disaster zones, (3) less consideration of evacuation barracks and routes, and (4) people's lower understanding and awareness. Through this research, we also discovered the proposed simple and easy-use method suitable for classifying the risks. The research was limited to Mount Merapi's resettlement housing after the 2010 eruption by examining five Huntaps with higher hazard susceptibilities. This study contributes to reevaluating the risk-hazard-resilience by practical measures for driving higher disaster awareness in the future. The proposed method proved its appropriateness in testing the risks and has the prospect of being used in further applications in more massive cases.